SENYAWA BARU PASCA KEBAKARAN PENYEBAB RAPUHNYA BETON BERTULANG - Lukman, Lukman (Universitas Diponegoro, 2007)
Abstract Fire can be happened everywhere at anytime, including to building which use reinforced concrete construction. As consequense of the fire. a heating and cooling cycle by turns happen which cause complex fisis and chemical phase chenge. Considering that concrete has teracity againts high temperature without having chemical compound coposition change because of the high silica, which is until 1000 EC of temperature Keyword The concrete after fire